Analysis of Nursing Graduate Theses Related to Gestational Diabetes in Turkey: A Systematic Review - Dural, Gül; Şener, Nurdilan (Izmir Katip Celebi University, 2023)
Objective: This study aims to review the master's and doctoral theses on gestational diabetes (GD) in the field of nursing in Turkey. Material and Method: The population of the study consisted of doctorate and master's theses conducted in the Nursing, Internal Medicine Nursing and Obstetrics and Gynaecology Nursing Departments and registered in the National Thesis Centre of the Council of Higher Education between 2000 and 2021. The keyword "gestational diabetes" was used in the study. Five doctoral and 12 master's theses were examined in the retrospective descriptive literature review. In the analysis of data, master's and doctoral theses were shown in different tables and their authors, publication years, departments, sample characteristics, data collection tools, methods and results were summarized. Results: Of the 12 master's theses reviewed, 11 are descriptive, one is methodological, of the five doctoral theses, one is semi-experimental and four are experimental. It has been found that depression and anxiety levels are high in pregnant women with GD, the frequency of GD is high, the quality of life is negatively affected, and breastfeeding problems are more common. It has been found that education and counselling services affect lifestyle behaviours and quality of life in pregnant women positively, reduce depression symptoms and increase compliance with pregnancy and GD. Conclusion: It has been determined that gestational diabetes is common in pregnant women and negatively affects their quality of life. It has been found that education and counselling services have a positive effect on women's health. It is recommended for nurses to conduct more experimental studies on GD that affects pregnant women.

Amaç: Bu çalışmada Türkiye’de hemşirelik alanında Gestasyonel Diyabet (GD) konusunda yapılan yüksek lisans ve doktora tezlerinin taranması amaçlanmıştır. Gereç ve Yöntem: Çalışmanın evrenini Yükseköğretim Kurulu Ulusal Tez Merkezi’ne kayıtlı 2000-2021 yılları arasında Hemşirelik, İç Hastalıkları Hemşireliği ve Doğum ve Kadın Hastalıkları Hemşireliği Anabilim Dallarında yapılan doktora ve yüksek lisans tezleri oluşturdu. Bu çalışmada “gestasyonel diyabet” anahtar kelimesi kullanıldı. Retrospektif tanımlayıcı literatür araştırmasında 5 doktora ve 12 yüksek lisans tezi incelendi. Verilerin analizinde yüksek lisans ve doktora tezleri farklı tablolarda gösterilip yazarı, yayın yılı, anabilim dalı, örneklem özellikleri, veri toplama araçları, yöntemi ve sonuçları özetlendi. Bulgular: Taranan 12 yüksek lisans tezinden 11’si tanımlayıcı, 1’i metodolojik; 5 doktora tezinden 1’i yarı deneysel, 4’ü deneyseldir. GD’li gebelerde depresyon ve anksiyete seviyelerinin yüksek olduğu ve GD sıklığının yüksek olduğu ve yaşam kalitesinin olumsuz etkilendiği ve emzirme problemlerinin daha fazla olduğu görülmüştür. Eğitim ve danışmanlık hizmetlerinin gebelerde yaşam biçimi davranışlarını ve yaşam kalitesini olumlu etkilediği ve depresyon semptomlarını azalttığı, gebeliğe ve GD’ye uyumu arttırdığı görülmüştür. Sonuç: Gestasyonel diyabetin gebelerde yaygın olarak görüldüğü ve yaşam kalitesini olumsuz etkilediği saptanmıştır. Eğitim ve danışmanlık hizmetlerinin kadınların sağlığını olumlu etkilediği görülmüştür. Gebeleri etkileyen GD’ye yönelik hemşireler tarafından daha çok deneysel araştırmaların yapılması önerilmektedir.
Türkiye’de Gestasyonel Diyabetle İlgili Hemşirelik Lisansüstü Tezlerin İncelenmesi: Sistematik Derleme
Keywords: Health Care Administration; Sağlık Kurumları Yönetimi